German Troops in Afghanistan: Strategic Narratives on German Participation in Resolute Support. Issue 2 (4th March 2022) - Kříž, Zdeněk
ABSTRACT: There are three basic strategic narratives about German engagement in Resolute Support in the German political debate: 'reconstruction of Afghanistan', 'war in Afghanistan' and 'futility of our efforts'. The first two have been present in the German debate on Afghanistan since 2001, while the 'futility of our efforts' narrative is new, gaining ground in the parliamentary debate in the last couple of years, in connection with the rise of AfD. The 'war in Afghanistan' narrative, which aims to demobilize public support for Afghan involvement, blames Germany for instability in Afghanistan. The 'futility of our efforts' narrative claims that focusing on the building of modern state institutions in Afghanistan and the promotion of human rights according to Western understandings are counterproductive, as far as achieving peace in the country is concerned. Only the 'reconstruction of Afghanistan' narrative aims to mobilize public support for participation in the Resolute Support mission. However, all three identified narratives can be used to support the current German policy of departure from Afghanistan.